(untitled) - Grisham, John (New York, 2003)
A washed-up public defender's latest case takes an unexpected turn when he discovers evidence of a conspiracy involving a large drug company and a lawsuit with a huge potential settlement.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy